Training of Future Physical Education and Sports Teachers in Higher Education Institutions: Modern Trends - Han, Liu (Pedagogical Discourse, 2024)
The article outlines the characteristics of professional training for future physical education and sports teachers in higher education institutions, emphasizing the social significance of such training and the standards for its quality. It highlights changes in the primary objectives of teacher training, which are driven by a consistent shift toward student-centered education and a contemporary focus on the personal development of specialists. From this perspective, the professional competence of a teacher is defined as a category that reflects the attained level of professional education, the pedagogical experience gained during training, and the individual professional abilities developed throughout the process. An analysis of the works of scientists and legislative documents related to the studied issues has been conducted. This analysis highlights the shortcomings and new requirements for the training of pedagogical personnel. Additionally, it reveals the multifaceted process of professional development for specialists in physical education and sports during their studies at higher education institutions. It is important to note that the systematic education of specialists in physical education and sports encompasses three key components that enhance pedagogical effectiveness: a sports-oriented worldview, emotional well-being, and competence in physical education and health improvement. Modern trends in the development of professional training systems for future teachers of physical education and sports are shaped by innovative approaches within higher education pedagogy and a creative strategy for planning the educational process. These trends emphasize personalized and individualized methods aimed at fostering comprehensive student development. They also incorporate integrated and health-promoting technologies in education, promote the internationalization of education, and support inclusive education. Current trends in professional training highlight project-based learning, psychological and pedagogical support, the cultivation of leadership qualities, and the modernization of educational program content. It is concluded that the professional training of future teachers is focused on developing well-rounded and competent specialists in higher education institutions, who are capable of fostering a healthy society and promoting physical educationand sports among citizens.